Structure and conservation of the periplasmic targeting factor Tic22 protein from plants and cyanobacteria - Tripp, Joanna; König, Patrick; Sinning, Irmgard; Tews, Ivo (The journal of biological chemistry, 2012)
Mitochondria and chloroplasts are of endosymbiotic origin. Their integration into cells entailed the development of protein translocons, partially by recycling bacterial proteins. We demonstrate the evolutionary conservation of the translocon component Tic22 between cyanobacteria and chloroplasts. Tic22 in Anabaena sp. PCC 7120 is essential. The protein is localized in the thylakoids and in the periplasm and can be functionally replaced by a plant orthologue. Tic22 physically interacts with the outer envelope biogenesis factor Omp85 in vitro and in vivo, the latter exemplified by immunoprecipitation after chemical cross-linking. The physical interaction together with the phenotype of a tic22 mutant comparable with the one of the omp85 mutant indicates a concerted function of both proteins. The three-dimensional structure allows the definition of conserved hydrophobic pockets comparable with those of ClpS or BamB. The results presented suggest a function of Tic22 in outer membrane biogenesis.